THE EFFECT OF VLOG HISTORY-BASED HISTORY LEARNING ON LEARNING ACTIVENESS AND HISTORICAL COMPREHENSION OF STUDENTS IN SENIOR HIGH SCHOOLS - Nurul Qhatami Musthafa; Wawan Darmawan; Yeni Kurniawati (SOSIOEDUKASI, 2025)
In the midst of 21st century learning demands that emphasize active participation and comprehensive student involvement, teachers can make learning meaningful by facilitating students to develop their historical understanding through innovative learning methods, models and strategies. The purpose of this study is to analyze the effect of the application of vlog history-based history learning on learning activeness and historical comprehension of students in experimental classes. The method used in this research is quantitative approach with quasi experiment method. This research design uses a non-equivalent pretest-posttest control group design. The results showed that n-gain testing on learning activeness data obtained a gain value of 0.4381 or 43.8120% with the category that the increase in student learning activeness in class XI 5 was moderate and n-gain historical comprehension testing obtained results of 0.8604 or 86.036% with a high gain category. The application of vlog history media in learning history is the answer to the demands of today's digital era learning, in vlog history shows the teacher as a content creator performs a contemporary digital visual style of learning to be able to encourage students' activeness in learning. The use of vlog history in history learning provides the latest way of delivering learning material that adapts the learning style of students to technological developments. The vlog history that teachers create can support the importance of 21st century competencies where the majority of students are digital natives.